M=-2/5 is the answer to this equation
Answer:
Step-by-step explanation:
4y - 2(5 - y + 4) = 4y - 2(9 - y)
= 4y + 9*(-2) - y *(-2)
= 4y - 18 + 2y {Combine like terms 4y and 2y}
= 6y - 18
6y - 18 = 6*y - 6*3
= 6(y - 3)
6y- 18 = 2 *3y - 2*9
= 2(3y -9)
2(3y - 9) and 6(y- 3 ) are equivalent to 4y - 2(5- y +4)
Others are not equivalent
Hi!
To compare this two sets of data, you need to use a t-student test:
You have the following data:
-Monday n1=16; <span>x̄1=59,4 mph; s1=3,7 mph
-Wednesday n2=20; </span>x̄2=56,3 mph; s2=4,4 mph
You need to calculate the statistical t, and compare it with the value from tables. If the value you obtained is bigger than the tabulated one, there is a statistically significant difference between the two samples.
![t= \frac{X1-X2}{ \sqrt{ \frac{(n1-1)* s1^{2}+(n2-1)* s2^{2} }{n1+n2-2}} * \sqrt{ \frac{1}{n1}+ \frac{1}{n2}} } =2,2510](https://tex.z-dn.net/?f=t%3D%20%5Cfrac%7BX1-X2%7D%7B%20%5Csqrt%7B%20%5Cfrac%7B%28n1-1%29%2A%20s1%5E%7B2%7D%2B%28n2-1%29%2A%20s2%5E%7B2%7D%20%7D%7Bn1%2Bn2-2%7D%7D%20%2A%20%5Csqrt%7B%20%5Cfrac%7B1%7D%7Bn1%7D%2B%20%5Cfrac%7B1%7D%7Bn2%7D%7D%20%7D%20%3D2%2C2510)
To calculate the degrees of freedom you need to use the following equation:
![df= \frac{ (\frac{ s1^{2}}{n1} + \frac{ s2^{2}}{n2})^{2}}{ \frac{(s1^{2}/n1)^{2}}{n1-1}+ \frac{(s2^{2}/n2)^{2}}{n2-1}}=33,89](https://tex.z-dn.net/?f=df%3D%20%5Cfrac%7B%20%28%5Cfrac%7B%20s1%5E%7B2%7D%7D%7Bn1%7D%20%2B%20%5Cfrac%7B%20s2%5E%7B2%7D%7D%7Bn2%7D%29%5E%7B2%7D%7D%7B%20%5Cfrac%7B%28s1%5E%7B2%7D%2Fn1%29%5E%7B2%7D%7D%7Bn1-1%7D%2B%20%5Cfrac%7B%28s2%5E%7B2%7D%2Fn2%29%5E%7B2%7D%7D%7Bn2-1%7D%7D%3D33%2C89)
≈34
The tabulated value at 0,05 level (using two-tails, as the distribution is normal) is 2,03. https://www.danielsoper.com/statcalc/calculator.aspx?id=10
So, as the calculated value is higher than the critical tabulated one,
we can conclude that the average speed for all vehicles was higher on Monday than on Wednesday.
Answer- 16
explanation- that’s what it is
Answer:
The number will be -13
Step-by-step explanation:
Let the no. be x
Its twice will be = 2x
According to the question ,
![2x + 7 = -19\\=> 2x = -19 - 7 = -26\\=> x = \frac{- 26}{2} = - 13](https://tex.z-dn.net/?f=2x%20%2B%207%20%3D%20-19%5C%5C%3D%3E%202x%20%3D%20-19%20-%207%20%3D%20-26%5C%5C%3D%3E%20x%20%3D%20%5Cfrac%7B-%2026%7D%7B2%7D%20%3D%20-%2013)